2009
DOI: 10.1371/journal.pone.0004398
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphatidylserine Targets Single-Walled Carbon Nanotubes to Professional Phagocytes In Vitro and In Vivo

Abstract: Broad applications of single-walled carbon nanotubes (SWCNT) dictate the necessity to better understand their health effects. Poor recognition of non-functionalized SWCNT by phagocytes is prohibitive towards controlling their biological action. We report that SWCNT coating with a phospholipid “eat-me” signal, phosphatidylserine (PS), makes them recognizable in vitro by different phagocytic cells - murine RAW264.7 macrophages, primary monocyte-derived human macrophages, dendritic cells, and rat brain microglia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 81 publications
1
85
2
Order By: Relevance
“…Much research has been carried out, such as the 0008-6223/$ -see front matter Ó 2011 Elsevier Ltd. All rights reserved. doi:10.1016/j.carbon.2011.01.003 targeted delivery of cisplatin into Ntera-2 cells by FA-modified SWCNTs [20], cytochrome C into phagocytic cells by phosphatidylserine-modified SWCNTs [21], gemcitabine into lymph nodes by NPs-modified multiwall carbon nanotube (MWCNT) [22], doxorubicin (Dox) into WiDr cells by antibody-modified SWCNTs [23] and other related researches [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been carried out, such as the 0008-6223/$ -see front matter Ó 2011 Elsevier Ltd. All rights reserved. doi:10.1016/j.carbon.2011.01.003 targeted delivery of cisplatin into Ntera-2 cells by FA-modified SWCNTs [20], cytochrome C into phagocytic cells by phosphatidylserine-modified SWCNTs [21], gemcitabine into lymph nodes by NPs-modified multiwall carbon nanotube (MWCNT) [22], doxorubicin (Dox) into WiDr cells by antibody-modified SWCNTs [23] and other related researches [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the lipid component, especially relevant for inhalation scenarios, also plays a crucial role for biorecognition 56 ; thus carbon nanotubes covered by a phospholipid uptake signal, phosphatidylserine, are recognised and cleared by macrophages both in vitro and following inhalation in vivo 57 .…”
mentioning
confidence: 99%
“…6 Other recent work described the enzymatic degradation of functionalized SWCNT in vitro and in vivo, offering the potential for metabolic decomposition of CNT drug constructs. [40][41][42][43] Further, toxicity studies have confirmed the safe in vivo use of functionalized SWCNT. [44][45][46][47] Taken together, these data on renal elimination, enzymatic degradation, and lack of toxicity support continued investigation of SWCNT as a platform in drug development.…”
mentioning
confidence: 86%